2009
DOI: 10.1074/jbc.m806173200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplet Biogenesis Induced by Stress Involves Triacylglycerol Synthesis That Depends on Group VIA Phospholipase A2

Abstract: This work investigates the metabolic origin of triacylglycerol (TAG) formed during lipid droplet (LD) biogenesis induced by stress. Cytotoxic inhibitors of fatty acid synthase induced TAG synthesis and LD biogenesis in CHO-K1 cells, in the absence of external sources of fatty acids. TAG synthesis was required for LD biogenesis and was sensitive to inhibition and down-regulation of the expression of group VIA phospholipase A 2 (iPLA 2 -VIA). Induction of stress with acidic pH, C 2 -ceramide, tunicamycin, or dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 53 publications
6
98
0
10
Order By: Relevance
“…[43][44][45][46] Recently, Gubern et al demonstrated that triglyceride synthesis and LD biogenesis during stress mainly takes place from pre-existing fatty acids and is dependent on group VI phospholipase A 2 (PLA 2 -VIA). 40 One possible explanation for LD accumulation is the impairment in mitochondrial fatty acid -oxidation, resulting from mitochondrial membrane damage, and leading to an increase in triglyceride storage. 14, 47,48 Results from our studies suggest that assessment of LD accumulation may serve as a biological marker of oxidative stress and indicate disrupted lipid homeostasis by nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46] Recently, Gubern et al demonstrated that triglyceride synthesis and LD biogenesis during stress mainly takes place from pre-existing fatty acids and is dependent on group VI phospholipase A 2 (PLA 2 -VIA). 40 One possible explanation for LD accumulation is the impairment in mitochondrial fatty acid -oxidation, resulting from mitochondrial membrane damage, and leading to an increase in triglyceride storage. 14, 47,48 Results from our studies suggest that assessment of LD accumulation may serve as a biological marker of oxidative stress and indicate disrupted lipid homeostasis by nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Cells generate LD from exogenous sources, free fatty acids or lipoproteins, but LD also appear in the absence of external lipids when cells are under stress, apparently after the recycling of membrane phospholipids into TAG (7). We have shown recently that group IVA PLA 2 (also termed cPLA 2 ␣) is required for LD biogenesis either after exogenous lipid loading (10) or during stress (7).…”
Section: Intracellular Lipid Droplets (Ld)mentioning
confidence: 99%
“…We have shown recently that group IVA PLA 2 (also termed cPLA 2 ␣) is required for LD biogenesis either after exogenous lipid loading (10) or during stress (7). Regardless of the LD-inducing situation, the enzyme is not involved in the synthesis of neutral lipids; rather, it allows the formation of LD from TAG-containing membranes.…”
Section: Intracellular Lipid Droplets (Ld)mentioning
confidence: 99%
See 1 more Smart Citation
“…Unsaturated fatty acids help cells to circumvent the toxicity of saturated fatty acid in mammalian cells by promoting TG production (Listenberger et al 2003). This function is also important in cardiomyocytes that are exposed to ischemia and reperfusion (Barba et al 2009), neurons during nutrient deprivation (Du et al (Gubern et al 2009). In Saccharomyces cerevisiae, a mutant lacking all lipid ester synthesis is viable under the normal conditions (Sandager et al 2002), but excess unsaturated fatty acids causes massive membrane proliferation and cell death ).…”
Section: General Lipid Droplet Functions Storage Of Lipid Estersmentioning
confidence: 99%